Effect of bilateral or single leg landing on knee kinematics - Abe, S.; Lewis, M.; Malliah, K.; Malin, P.; Jensen, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Non-contact anterior cruciate ligament (ACL) injury has been shown to be more common in women than men, occurring at a rate of 6-8 times that of men (Hughes et al. (2008). Causes for this discrepancy are unknown, but differences in knee landing angle have been suggested as a possibility. Kinematic variables have been shown to be a major predictor in peak anterior tibial shear force (Schultz et al., 2009). Hughes et al. (2008) found that women display greater valgus angles and range of motion than men in a two legged landing. While Elvin et al. (2007) reported that knee contact angle was correlated to ground reaction forces and segment axial accelerations. Thus while it appears that knee kinematics are an important factor determining the stress on the knee in bilateral drop landings, in many cases, individuals cannot land on both legs and instead are forced to landing on a single leg. However, there is information lacking comparing knee joint angle and acceleration when landing on one versus two legs and these variables affect soft tissue forces on the knee. The purpose of this study was to compare knee joint range of motion and angular acceleration of the right and left leg during bilateral and single leg landings for males and females.